Κοινωνικές ιεραρχίες στα κείμενα του Πλήθωνα και τα πρότυπά τους - ΣΜΑΡΝΑΚΗΣ Γιάννης (Byzantina Symmeikta, 1998)
Yannis Smarnakis Social Hierarchy in Pletho and its Models The subject of this paper are the models of social organization proposed by G. Gemistos-Plethon to the despot of Peloponnese Theodore II Palaeologus and to the emperor Manuel II Palaeologus. The main sources for the investigation are two texts, written by Plethon, the first one between 1407-1415 and the second in 1418. The older text that was sent to the despot Theodore, depends on the platonic dialogues and proposes a similar model of three classes for the peloponnesian society. An interesting ideological shift was detected in the second text of 1418. Here the author proposes the division of the peloponnesian people into three parts, the soldiers, the priests and the peasants. The new model is identical to the ideological system of the three classes or functions in medieval France. I think that the main source of inspiration for Plethon was the specific ternary model that was grounded, in medieval France, on the neoplatonic tradition. Plethon transfers this ideological system to the social reality of his contemporary Peloponnese that was marked by the struggle of the powerful local aristocracy against the institution of monarchy. The ternary model gives a stable form to the peloponnesian society, justifies the role of the military aristocracy as the state against the Turks and legitimatizes the place of the monarch as the sovereign of the soldiers at the top of the social pyramid.